Complex contraception provision during the COVID-19 pandemic, how did sexual health services fare?. (April 2022) - Datsenko, Anna; Marriott, Amelia; Shaw, Jessica; Patel, Raj; Foley, Elizabeth
Background: This study evaluated whether sexual health services (SHS) across the UK could meet the Faculty of Sexual and Reproductive Health (FSRH) standard for access by being able to offer an appointment for a long-acting reversible contraception (LARC) fitting within 2 weeks of initial contact. Methods: SHSs offering LARCs were identified using the British Association for Sexual Health and HIV (BASHH) clinic database. During October 2020, all clinics open for more than 1 day a week were contacted by telephone. The researcher posed as a 20-year-old woman in a regular heterosexual relationship who was using condoms and requesting a contraceptive implant. Data collected included the time to wait to appointment and whether clinics offered bridging methods of contraception during any delay in appointment. It was also noted whether a local COVID-19 restriction was in place at the time of the call. The information collected was coded, and data was analysed using chi-square tests in SPSSv27. Results: Of the 218 contactable clinics, 51.4% ( n = 112) of clinics offered the patient an appointment within two weeks, and 66.1% ( n = 144) of clinics could offer appointments within four weeks. 7.3% ( n = 16) of clinics offered the patient adjunct bridging oral contraception until the time of appointment. Comparing the devolved nations, 11/17 (64.7%) clinics in Scotland, 8/13 (61.5%) clinics in Wales, 0/4 (0.0%) clinics in Northern Ireland and 93/182 (51.1%) clinics in England offered an appointment within two weeks with significant regional variation across England ( p = .005). No statistically significant difference was demonstrated in access between clinics with or without high-level COVID-19 restrictions ( p = .056). Conclusion: The 2-week standard was met in just over half of the occasions, with significant variation across regions across the UK. The development of a national target for access may improve access to LARCs.